Digitalizing Green Fashion Design via Service-Learning to Empower Fashion SMEs - Nasution, Rizki Amelia; Tarigan, M. Faisal Afiff; Mirza, Mohammed Aquil (Jurnal IPTEK Bagi Masyarakat, 2025)
This community service research introduces a model of digitalizing green fashion through a service-learning approach implemented at Rumah Jahit Nila, a fashion MSME in Medan. The intervention includes intensive training on 3D design software such as CLO 3D and Marvelous Designer, the use of AI-assisted tools like Repsketch for pattern optimization, and production mentoring throughout a 12-month project cycle. Measurements show an increase in students' average technical competency scores from 55.1 to 76.9, representing a gain of 21.8 points. Partner evaluation was conducted through satisfaction questionnaires and field observations, both of which indicated positive acceptance of digital patterns and user guides. Claims regarding waste reduction and material efficiency are currently indicative, as direct quantitative metrics such as percentage reduction in fabric use or paper pattern sheets are not yet available; thus, further measurement is recommended. This study offers a replicable digital technology-based community service model for empowering sustainable fashion MSMEs.